The Cost-Effectiveness of Home-Based Provision of Antiretroviral Therapy in Rural Uganda - Marseille, Elliot (2009)
CONTEXT: Highly active anti-retroviral therapy (ART) provides dramatic health benefits for HIV-infected individuals in Africa, and widespread implementation of HAART is proceeding rapidly. Little is known about the cost and cost-effectiveness of HAART programs. OBJECTIVE: To determine the incremental cost-effectiveness of a home-based HAART program in rural Uganda. DESIGN, SETTING AND PATIENTS: Computer-based, deterministic cost-effectiveness model to assess a broad range of economic inputs and health outcomes. From the societal perspective we compared the cost-effectiveness of HAART and cotrimoxazole prophylaxis with cotrimoxazole alone, and with the period before either intervention. Data for 24 months were derived from a trial of HAART in 1,045 patients in Tororo District in eastern Uganda. Costs and outcomes were projected out to 15 years. All costs are in 2004 U.S. dollars. INTERVENTIONS: First-line HAART regimen consisted of standard doses of stavudine, lamivudine, and either nevirapine or, for clients with active tuberculosis, efavirenz. Second-line therapy consisted of tenofovir, didanosine, and lopinavir/ritonavir. For children, first-line HAART consisted of zidovudine, lamivudine and nevirapine syrup; second-line therapy was stavudine, didanosine and lopinavir/ritonavir. MAIN OUTCOME MEASURES: HAART program costs, the health benefits accruing to HAART recipients, averted HIV infections in adults and children, and resulting effects on medical care costs. RESULTS: The HAART program standardized for 1,000 patients cost an incremental $1.39 million in its first two years. Compared with cotrimoxazole prophylaxis alone, the program reduced mortality by 87%, and averted 6,861 incremental disability adjusted life-years (DALYs). Benefits accrued from reduced mortality in HIV-infected adults, (67.5% of all benefits), prevention of death in HIV-negative children (20.7%), averted HIV infections in adults (9.1%) and children (1.0%), and improved health status (1.7%). The net program cost, including the medical cost implications of these health benefits was $4.09 million. The net cost per DALY averted was $597 compared with cotrimoxazole alone. Many HIV interventions have a cost-effectiveness ratio in the range of $1 – $150 per DALY averted CONCLUSIONS: A home-based HAART program in rural Africa was more cost-effective than most previous estimates for facility-based HAART programs, but remained less cost-effective than many HIV prevention and care interventions, including cotrimoxazole prophylaxis.